A development of portal: career and employer relation department / Abd Kadir Abdul Rahman - Abdul Rahman, Abd Kadir (2005)
This final project is mainly about; creating a portal for CERD (Career and Employer Relation Department) by using the web programming language know as ASP (Active Server Page), Microsoft Access as the database management system and IIS (Internet Information Service) as the server. The main objective of this research is to design a system with the concept of portal. It enables CERD to provide online service for it clients and it operation could be done through the internet. The most significance things to design this portal are to create jobseekers registration, job advertisement and employer registration through the networking system. The SDLC method is used in order to design this portal as for the convenient the structured approached has been choose to design a user interface in a simple, user friendly and consistent.